Predictors of the utilisation of continuum of maternal health care services in India - Sumirtha Gandhi; Supriya Gandhi; Umakant Dash; M. Suresh Babu (BMC, 2022)
Abstract Background Utilisation of continuum of maternal health care services is crucial for a healthy pregnancy and childbirth and plays an important role in attaining Universal Health Coverage (UHC) and Sustainable Development Goals (SDGs) related to maternal and child health. This paper aims to assess the percentage of dropouts across various stages of utilization of continuum of maternal health services (CMHS) in India and also investigates the factors hindering the utilization of these services. Methods We used recent data from National Family Health Survey(NFHS) encompassing a total sample of 1,70,937 pregnant women for the period 2015-16. The percentage of women dropping out while seeking maternal health care is measured using descriptive statistics. While, the factors impeding the utilization of maternal health services is estimated using a Multinomial Logistic Regression Model, where dependent variable (CMHS) is defined as complete care, incomplete care and no care. Results Only17% of pregnant women availed the utilisation of complete care and 83% either did not seek any care or dropped after seeking one or two services. For instance, it is found that 79% of women who registered for antenatal care services (ANC) did not avail the same adequately. An empirical investigation of determinants of inadequate utilization of CMHS revealed that factors like individual characteristics, for instance- access to media (RRR: 2.06) and mother's education play (RRR: 3.61) a vital role in the uptake of CMHS. It is also found that the interaction between wealth index and place of residence plays a pivotal role in seeking complete care. Lastly, the results revealed that male participation (RRR: 2.69) and contacting multi-purpose worker (MPW) (RRR: 2.33) are also at play. Conclusion The study suggests that the major determinants of utilisation of CMHS are access to media, mother's education, affordability barriers and male participation. Hence, policy recommendations should be oriented towards strengthening these dimensions and the utilisation of adequate ANC has to be considered as the need of the hour.